Perbedaan Kepuasan Belanja Online dan Offline - Fahleti, Widya Hana (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
Everyone sees different behavior when shopping online and offline. It is important for online marketers to recognize and understand these differences in online and offline shopping satisfaction when formulating marketing strategies that can further influence consumer satisfaction. The aim of this research is to determine the difference in satisfaction with online and offline shopping in Kutai Kartanegara. The population in this study was the Kutai Ketanegara community, the sample obtained was 196 consisting of 98 respondents who bought clothes online and 98 respondents who bought clothes offline. The data obtained were analyzed using the Mann Whitney method. The research results showed that there was a difference in satisfaction with online and offline shopping in Kutai Kartanegara Regency, from the mean comparison, it showed that satisfaction with online shopping was higher than offline shopping.